Magnetic recoverable nanomaterials: An efficient strategy for synthesis of pyrroles. Issue 20 (17th October 2020) - Aqeel Ashraf, Muhammad; Liu, Zhenling; Yang, Yafeng; Zhang, Dangquan
Abstract: Pyrrole structural fragments have exhibited many biological and pharmacological activities like antiallergic, immunosuppressive, anticancer, antibiotic, antitumor and anti-HIV activities. During the last decade, the catalytic potential of various magnetically recoverable nanomaterials have investigated for preparation of pyrrole structural fragments. In this paper, we provide an overview of the catalytic potential of magnetic nanomaterials for synthesis of pyrrole structural fragments. Graphical Abstract: